Pendampingan Pengadaan Bak Sampah “Ecoklagen” Untuk Menjaga Kelestarian Lingkungan Secara Berkelanjutan Di Desa Klagen Kabupaten Nganjuk - Fawasal Anas Fatlurrahman; Nurul Nurhidayati; Oktaviani Arcici Hadir; Siti Fatimah Jasmine; Diwangkoro Prasojo; Chrystia Aji Putra (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Waste management is a big problem that often occurs in Indonesia which can affect society and health. The waste management system implemented by the Klagen village community is not yet good, this can be seen from the village community who still throw rubbish carelessly and do not separate organic and non-organic waste. The aim of implementing this activity is to create a more efficient waste disposal medium in Klagen village. This activity was carried out using observation, discussion and implementation methods. It is hoped that the presence of trash cans in Klagen Village will provide significant changes in the future for the preservation and sustainability of the environment in Klagen Village. Of course, cooperation from the village is also expected so that it can continue the waste bin project that the KKN students have created.